Investigating the Effects of Admission-Related Stress on College Faculty in the Pondicherry Region - Dr. P. Kamaludeen,; M. Rajeswari, (International Journal of Engineering and Management Research, 2024)
This study explores the impact of admission-related stress on college faculty members in the pondicherry region, focusing on both psychological and professional dimensions. Utilizing a mixed-methods approach, the research involved surveying and interviewing faculty across various colleges to identify key stressors and assess their effects on faculty well-being and job performance. Findings indicate that a significant proportion of faculty experience high levels of stress during the admissions period, which adversely affects their mental health and professional efficiency. Key factors contributing to this stress include increased administrative workload, heightened expectations from students and parents, and inadequate institutional support. Additionally, demographic variables such as age, experience, and departmental affiliation influence stress levels, with younger and less experienced faculty reporting higher stress. The study also highlights effective coping mechanisms and institutional policies that can mitigate stress, suggesting the need for comprehensive support systems and stress management resources. These insights aim to inform policy recommendations to improve faculty well-being and enhance the overall educational environment.